Analisis Kelayakan Usaha Mikro Syariah sebagai Instrumen Pemberdayaan UMKM: Studi pada UMKM Kuliner Malam di Betungan Kota Bengkulu - Alda Julianti; Yosy Arisandy; Miko Polindi (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the success factors of sharia micro-enterprises, understand the perspectives of MSMEs on sharia-based empowerment, and assess the feasibility of sharia micro-enterprises among night culinary MSMEs in Betungan, Bengkulu City. The method used is descriptive qualitative, with data collection techniques conducted through observation, in-depth interviews, and documentation to ensure data validity and richness. The informant selection technique in this study used purposive sampling, which is a method of selecting samples based on specific considerations aligned with the research objectives and relevance to the study context. The results show that business success is influenced by several factors, including the length of business operation, level of income, strategic location, and the consistent application of sharia values in business practices. Furthermore, sharia micro-enterprises are considered quite feasible to run because they have fulfilled halal principles and demonstrated the ability to generate sustainable profits, although challenges remain, particularly in terms of legal compliance and the limited scope of empowerment support programs available.